MEDICATION ADHERENCE IN TYPE 2 DIABETES MELLITUS PATIENTS WITH CORONARY HEART DISEASE - Shafiero Muhammad Elsya Putera; Sony Wibisono; Andrianto; Hermina Novida (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights Type 2 diabetes mellitus (T2DM) that is not appropriately handled can result in macro- or micro-complications. Medication adherence is one of the most important efforts to do to prevent complications in chronic diseases such as T2DM. Abstract Background: Diabetes medication non-adherence can aggravate the patient's condition and raise the chance of acquiring diabetes complications such as coronary heart disease. Medication adherence can help prevent micro- and macrovascular problems. Objective: This study aimed to investigate the medication adherence of type 2 diabetic patients with coronary heart disease. Material and Method: This research used a systematic literature review for the research design, with a PRISMA chart as a guideline. Researchers searched 3 databases using predefined keywords: PubMed, Google Scholar, and ScienceDirect. Result: The search yielded 3.373 pieces of literature, and six pieces that fit the requirements were chosen. The total number of people who responded was 9.950. More men over 60 years old who have had diabetes for more than 5 years, who are taking oral medication, insulin, or combination treatment, and who are ex-smokers were shown to have characteristics of people with type 2 diabetes mellitus and coronary heart disease. Results from a systematic literature review revealed five kinds of literature with low medication adherence levels and one literature with a high medication adherence rate. Conclusion: Medication adherence differs among type 2 diabetic patients with coronary heart disease. More research, however, has revealed that the level of medication adherence in type 2 diabetic patients with coronary heart disease remains low.